Meningkatkan Hasil Belajar Siswa PPKN Pada Materi Menghargai Lingkungan Budaya Dan Jasa-Jasa Lokal Model Pembelajaran PJBL Mata Pelajaran PPKN - Suharyanti (Yana Research, 2023)
Student motivation is primarily PPKN education. However, in reality, students' abilities in PPKN lessons are still very low. For this reason, researchers conducted research with the aim of improving PPKN student learning outcomes on material respecting the cultural environment and local services in PPKN subjects in Class VII of SMP Negeri 3 Pintu Rime Gayo, Bener Meriah Regency, Aceh Province for the 2021 academic year. There are 19 students. After discussion, the situation found was that students thought that the material was difficult and they never put it into practice in learning. Students do not understand examples of local culture and examples of local services. Apart from that, the PPKN test results also showed an average score of 65 where only 40% of students passed the KKM. After using the PJBL learning model, PPKn learning motivation increased, the researchers also carried out an evaluation by giving a quiz in the form of multiple choices and from the results the scores that could be seen were very good. After my analysis, of the 19 students, only 2 were less than the KKM, while 18 students (90%) got scores above the set KKM.